Aplasia Cutis Congenita with Fetus Papyraceus: A Rare Case Report - Cristina, Catarina (2020)
Aplasia cutis congenita is a rare disorder, characterized by the absence of skin tissue at birth. Most commonly occurs as a solitary cutaneous defect on the scalp. It can be classified into 9 phenotypes according to the Frieden’s Classification System. We report a clinical case of a newborn, who was noted on physical examination, to have a large, symmetrical and well delimited lesions of absent skin, bilaterally at flanks, and a similar lesion on the right thigh. A monochorionic, diamniotic twin pregnancy, with intrauterine fetal death of one twin at 13 weeks of gestation. This illustrates, a very rare case (about 40 cases reported in the literature), of type V aplasia cutis congenita (associated with fetus papyraceus), with multiple and large area involvement. Despite the extent of the lesions, surgical therapy was not necessary, and conservative treatment was sufficient and effective.